The Relationship Between Mothers' Knowledge and Undernutrition Status in Toddlers at the Matahari and Sekar Wangi Integrated Health Posts in the Working Area of the Pahandut Community Health Center in Palangka Raya - Putri Ayu Lestari (PROMOTOR, 2026)
Background: Malnutrition in toddlers remains a serious public health issue, particularly in Palangka Raya, Central Kalimantan, where prevalence rates are above the national average. Maternal knowledge plays a pivotal role in ensuring adequate nutrition and preventing undernutrition in early childhood. This study aimed to examine the relationship between maternal nutritional knowledge and the nutritional status of toddlers at Posyandu Matahari and Sekar Wangi in the working area of Puskesmas Pahandut. Method: This study employed a cross-sectional design with a correlational approach. A total of 65 respondents were selected using the Slovin formula with a 5% margin of error. Data were collected through structured questionnaires assessing maternal knowledge, while children’s nutritional status was determined using weight-for-age Z-scores in accordance with WHO standards. Data were analyzed using Chi-square statistical tests to identify the relationship between maternal knowledge and child nutritional status. Results: Findings revealed that 47.7% of mothers had low knowledge, 40% moderate, and 12.3% good knowledge. Among toddlers, 67.7% had normal nutritional status, 24.6% were undernourished, and 7.7% were at risk of overnutrition. Chi-square analysis indicated a significant relationship between maternal knowledge and toddler nutritional status (p = 0.001). Conclusion: Maternal nutritional knowledge significantly influences toddler nutritional outcomes. Improving maternal knowledge through health education and community-based interventions is essential to reduce undernutrition prevalence and promote child health.